2018
DOI: 10.1093/jncics/pky061
|View full text |Cite
|
Sign up to set email alerts
|

Population Frequency of Serous Tubal Intraepithelial Carcinoma (STIC) in Clinical Practice Using SEE-Fim Protocol

Abstract: Frequent detection of serous tubal intraepithelial carcinoma (STIC) among BRCA1/2 mutation carriers undergoing risk-reducing surgery prompted the hypothesis that many adnexal high-grade serous carcinomas (HGSCs) arise from the fallopian tube, rather than the ovary, as supposed. The changing paradigm has important implications for HGSC prevention. Most data related to the frequency of STIC are derived from case series and estimates vary widely. Therefore, we analyzed population-based data from 10 523 surgeries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
0
22
1
Order By: Relevance
“…Additionally, a careful consideration of the global changes in the fallopian tube with STIC lesions could simplify the current protocol for pathologic examination of fallopian tubes. Since early cancer lesions are typically microscopic, entire fallopian tubes are cut into thin sections using the SEE-FIM (sectioning and extensive examination of the fimbria) dissection protocol with the distal fimbriae cut sagittally at 1 mm intervals ( 21 ). This can yield a large number of slides that need to be reviewed by a pathologist to potentially identify one section with an early cancer lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a careful consideration of the global changes in the fallopian tube with STIC lesions could simplify the current protocol for pathologic examination of fallopian tubes. Since early cancer lesions are typically microscopic, entire fallopian tubes are cut into thin sections using the SEE-FIM (sectioning and extensive examination of the fimbria) dissection protocol with the distal fimbriae cut sagittally at 1 mm intervals ( 21 ). This can yield a large number of slides that need to be reviewed by a pathologist to potentially identify one section with an early cancer lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was not set up to assess the prevalence of STIC lesions or cancer, and a SEE‐FIM protocol is not used routinely for grossly normal tubes removed from women with no increased risk of ovarian cancer (as opposed to specimens from women with a BRCA mutation). A recent Canadian study that used the SEE‐FIM protocol found STIC in eight of 9392 women (less than 0·1 per cent) with benign diagnoses who had a normal risk of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, of the 31 older patients, 1 was diagnosed with a stage 2 malignancy and 2 were diagnosed with STIC lesions (6.5%), which is a higher rate than 1%-2% reported STIC identification during RRSO. 15,16 Arguably, the one malignancy that may have been prevented with earlier participation in a screening program.…”
Section: Practice Implications and Research Recommendationsmentioning
confidence: 99%